Catalytic performances of silicotungstic acid/zirconia supported SBA-15 in an esterification of benzyl alcohol with acetic acid - Sawant, Dhanashri P.; Vinu, A.; Justus, Josena; Srinivasu, P.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Liquid phase esterification of benzyl alcohol (BA) to benzyl acetate (Peach fragrance) with an acetic acid (AA) has been investigated with 12-silicotungstic acid supported on zirconia embedded inside SBA-15 (STA/ZrO2/SBA- 15) as the catalyst. Catalysts were unambiguously characterized by XRD, N-2 adsorption-desorption, FF-IR pyridine adsorption techniques and the total amount of acidity of different STA loaded catalysts was estimated by TPD of NH3. The optimization of reaction conditions of an esterification of BA with AA was performed with 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K by varying catalyst concentration (1-10 wt.% of reaction mixture); temperature, 353-383 K and AA:BA molar ratio as 0.5-3. The 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K was found to have the highest acidity and more active in the reaction. Under the optimized reaction conditions, the 15 wt.% STA/22.4 wt.%ZrO2/SBA-15 calcined at 1123 K gave 59% BA conversion with selectivity for benzyl acetate as high as 96% within 2 h of reaction time. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: 12-silicotungstic acid; Benzyl acetate; Benzyl alcohol; Esterification; SBA-15

Cyclohexylation of resorcinol with cyclohexanol catalyzed by tungstophosphoric acid supported zirconia catalysts - Balasubramanian, V. V.; Devassay, B. M.; Halligudi, S. B.; Deepika, R.; Umbarakar, S. B.; Vinu, A. (Journal of Nanoscience and Nanotechnology, 2018)
We demonstrate a highly active and reusable heterogeneous catalyst system, tungstophosphoric acid (TPA) supported on zirconia (ZrO2), for the cyclohexylation of resorcinol by cyclohexanol to produce value added chemicals such as 2-cyclohexyl resorcinol, 4-cyclohexyl resorcinol and 3-Hydroxy cyclohexyl phenyl ether under liquid phase reaction condition. TPA/ZrO2 catalysts prepared with different TPA loadings (5-30 wt.%) by wet impregnation method and calcined in the temperature range of 650-850 degrees C were characterized by Nitrogen sorption analysis, XRD, FTIR, DTG and DTA, and P-31 MAS NMR spectroscopy. Among the catalysts studied, 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C gave the highest conversion of resorcinol (51.2%) with the selectivities for 3-Hydroxy cyclohexyl phenyl ether (53.9%) and 2-cyclohexyl resorcinol and 4-cyclohexyl resorcinol together (46.1%) under optimum reaction conditions. However, the selectivity of the products were controlled by varying the reaction conditions. At higher conversion of resorcinol (78.9%), only C-alkylated products were formed at 200 degrees C with 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C. The combination of TPA and ZrO2 coupled with calcination temperature offered an excellent platform for the conversion of resorcinol into O- or C-alkylated products.
Keywords: 15% TPA/ZrO2; Cyclohexanol; Cyclohexylation; Keggin TPA; Resorcinol